Analysis of effects of multipath signal with nonuniform Doppler shift on vertical underwater acoustic communication. (18th June 2018) - Deguchi, Mitsuyasu; Kida, Yukihiro; Watanabe, Yoshitaka; Shimura, Takuya
Abstract: In this research, effects of a multipath signal with a nonuniform Doppler shift on underwater acoustic communication between surface and underwater vehicles are investigated by simulation. Single-carrier modulation (SCM) and orthogonal frequency domain multiplexing (OFDM) are utilized and the Doppler shift is caused by the roll motion of the surface vehicle. In SCM communication, it is revealed that a decision feedback equalizer suppresses effects of the phase shift of the multipath signal caused by the nonuniform Doppler shift. On the other hand, a resampling method is proposed and utilized to evaluate the performance of OFDM demodulation after removing the effects of the nonuniform Doppler shift of the direct signal. Consequently, it is shown that the Doppler shift of the multipath signal causes intercarrier interferences even with the method. Furthermore, it is demonstrated that OFDM communication is more sensitive to the Doppler shift of the multipath signal than SCM communication.